Efficiency of natural substances to protect Beauveria bassiana conidia from UV radiation. Issue 2 (25th October 2018) - Kaiser, Deborah; Bacher, Sven; Mène‐Saffrané, Laurent; Grabenweger, Giselher
Abstract: BACKGROUND: Solar radiation is assumed to be a major factor limiting the efficacy of entomopathogenic fungi used as biocontrol agents in open field applications. We evaluated 12 natural UV‐protective co‐formulants for their effect on the survival of UV‐exposed Beauveria bassiana spores on agar plates, colza leaf discs and in the field. RESULTS: Colony‐forming unit (CFU) counts of unformulated conidia on agar plates and leaf discs dropped to ≤ 50% after exposure to UV radiation. The highest UV protection was achieved with humic acid, which provided > 90% protection of UV‐B‐exposed conidia in laboratory experiments. In the field, 10% humic acid increased spore persistence up to 87% at 7 days after application. Sesame and colza oil also provided high UV protection in both assays (> 73% and > 70%, respectively). CONCLUSIONS: This study shows that it is possible to increase the persistence of B. bassiana spores under exposure to UV radiation by formulation with natural UV‐protective additives. UV protectants might, therefore, increase the efficacy of entomopathogenic fungi as biocontrol agents in open field applications. © 2018 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. Abstract : We evaluated natural UV‐protective co‐formulants for their effect on UV‐exposed Beauveria bassiana spores and present humic acid as a novel UV‐protective substance with confirmed protection under laboratory and field conditions.